Sociocultural contexts of language and literacy - Pérez, Bertha, 1945-; McCarty, T. L. (Lawrence Erlbaum, 2004)
Nine American academics, educational consultants, and bilingual/bicultural program development specialists contribute 12 chapters in a research- and theory-based text about learning and teaching in linguistically and culturally diverse classrooms. The second edition features updated research on multilingual and second-language literacy, and the int.